Identifying Obstacles and Solutions in the Cassava Chips Production Process at PT. Sinar Utami, Paseh Village, Sumedang Regency - Hidayat, Nita Puspita Anugrawati; Dariah, Atih Rohaeti; Irfani, Aminudin; Mahfudz, Muhammad Syarqim; Melia; Abdullah, Gelar (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
Cassava chips are a highly sought-after treat for Indonesian people. PT. Sinar Utami is a microbusiness located in Paseh Village, Sumedang Regency, producing cassava chips by involving housewives as production partners. This research aims to identify obstacles in the production process of cassava chips and discover solutions to increase production efficiency. The research methods used include observation, questionnaires, and interviews. The research results reveal that the obstacles in production are the manual milling, pressing, and cutting processes, which require a long time. Drying depends on the weather, as well as on dust that sticks to it during the drying process. In addition to that, there are challenges with production partners concerning skill gaps and accuracy. An analysis of economic aspects indicates that PT. Sinar Utami positively contributes by creating job opportunities for local workers, which enhances their household incomes. To overcome production constraints, we have designed simple tools aimed at improving efficiency. Meanwhile, regarding obstacles with production partners, we recommend organizing a seminar focused on fostering appropriate work attitudes in line with Islamic principles. We hope this research will support PT. Sinar Utami to boost cassava chips to meet the growing market demand.